Exact Solutions and Conservation Laws of a (2+1)-Dimensional Nonlinear KP-BBM Equation - Khadijo Rashid Adem; Chaudry Masood Khalique (Abstract and Applied Analysis)
In this paper, we study the two-dimensional nonlinear Kadomtsov-Petviashivilli-Benjamin-Bona-Mahony (KP-BBM) equation. This equation is the Benjamin-Bona-Mahony equation formulated in the KP sense. We first obtain exact solutions of this equation using the Lie group analysis and the simplest equation method. The solutions obtained are solitary waves. In addition, the conservation laws for the KP-BBM equation are constructed by using the multiplier method.